PERANCANGAN APLIKASI PEMESANAN BERBASIS ANDROID PADA JASA LAUNDRY (STUDI KASUS ARFA LAUNDRY SERPONG) - Fauzan, Alif Raihanza; Vany Terisia; Shevti Arbekti Arman (Jurnal Sistem Informasi (JUSIN), 2023)
At this time, laundry service is a facility that is widely used by people with the density of activities carried out and limited time to do household tasks, especially in terms of washing and ironing clothes, therefore people prefer laundry services. However, in the current system there is no application that can make it easier for owners or customers to make the process of ordering laundry services and the ordering process is still done manually. To overcome these problems, researchers have provided a solution in the form of designing an Android-based laundry service application to facilitate the ordering process for laundry business owners and make it easier for customers in the process of ordering services. In designing this application the method used is waterfall. This waterfall method is executed sequentially, starting from the initial stage to the final stage, where each stage must be completed before starting the next stage. In the process of making it using Android Studio with the Java programming language and for database storage using Firebase. An android-based laundry service application designed for laundry services aims to improve service efficiency by facilitating laundry owners in receiving orders digitally, as well as helping customers in the process of ordering laundry services through their Android devices.